2019
DOI: 10.3390/ijerph16183283
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Dental Filling Materials and the Risk of Dementia: A Population-Based Nested Case Control Study in Taiwan

Abstract: When studying the range of toxic substances triggering dementia, special attention should be paid to the materials used in dental practice, particularly to dental fillings containing amalgam. This necessitated conducting large-scale epidemiologic studies. The aim of our research was to determine the risk factors for developing dementia when filling materials containing amalgam are used in dental practice. In order to achieve the set goals, the following tasks were undertaken: (1) The social and demographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
1
0
6
Order By: Relevance
“…In spite of the proven survival superiority of metal-colored fillings in some clinical scenarios [45], the current study found some patients who refuse this treatment option. The refusal is due to the controversies regarding mercury safety [50] and the aesthetic look [48,51]. It happens that patients do not attend another appointment after the diagnosis has been made.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the proven survival superiority of metal-colored fillings in some clinical scenarios [45], the current study found some patients who refuse this treatment option. The refusal is due to the controversies regarding mercury safety [50] and the aesthetic look [48,51]. It happens that patients do not attend another appointment after the diagnosis has been made.…”
Section: Discussionmentioning
confidence: 99%
“…Rtęć pochodząca z tych źródeł powoduje znaczące skażenie wody, powietrza oraz żywności, co w konsekwencji przyczynia się do negatywnego wpływu na zdrowie jednostek. Rtęć w środowisku i w wodach gruntowych jest biotranformowana przez mikroorganizmy do metylortęci [2][3][4][5][6][7].W 2017 roku została przyjęta Konwencja Minamata, która powzięła za cel ochronę środowiska oraz zdrowia ludzi przed niekorzystnym wpływem rtęci i jest międzynarodowym traktatem środowiskowym. Norwegia jako pierwsza wprowadziła zakaz stosowania rtęci w produktach, dotyczyło to również wycofywania stosowania amalgamatów dentystycznych, w jej ślady następnie poszły Szwecja i Dania.…”
Section: Wprowadzenieunclassified
“…Rtęć kumuluje się i ulega addycji przez wiele tysięcy lat, a najwyższe stężenie osiąga w organizmach na końcu łańcucha pokarmowego, jakimi są ludzie i ryby drapieżne [2,3]. Badania donoszą, że rtęć powoduje wiele zaburzeń fizjologicznych i niesie za sobą niekorzystne skutki medyczne, rozpoczynając od bioakumulacji w ośrodkowym układzie nerwowym, nerkach i wątrobie, przyczyniając się do uszkodzenia nerek, immunotoksyczności, genotoksyczności, spadku płodności oraz zmiany funkcjonowania osi endokrynologicznych [4,5,7,[16][17][18][19][20]. Amalgamaty stosowane do wypełniania ubytków w stomatologii stanowią główne i przewlekłe źródło narażenia pacjentów na nieorganiczną rtęć [6,14].…”
Section: Wprowadzenieunclassified
See 2 more Smart Citations